Using learning styles and viewing styles in streaming video - De Boer, J.; Kommers, Petrus; De Brock, B. (Pergamon, 2011)
Improving the effectiveness of learning when students observe video lectures becomes urgent with the rising advent of (web-based) video materials. Vital questions are how students differ in their learning preferences and what patterns in viewing video can be detected in log files. Our experiments inventory students' viewing patterns while watching instructional videos. Four viewing styles were postulated and checked for correlations with existing learning styles and the recent signaling of parallels with the learner's short-term memory capacity. Finally we checked whether learners' awareness of their actual viewing style potentially contributed to learning outcomes. The viewing behavior of 50 undergraduate students has been investigated. The students performed an individual learning task based upon instructional videos. Felders learning styles test and Huai's short-term memory test were used and checked for correlation. Video recordings in a usability lab were used to measure the students' viewing behavior. A multiple-choice test was integrated to measure possible learning effects. Moreover, students were interviewed afterwards. No strong correlation between the viewing styles and pervasive personal traits of students was perceived. Some students seem to switch their viewing style based upon their cognitive need, without lowering their test score. This flexibility of the student in adapting his viewing behavior might account for the missing correlation between pervasive personality traits and viewing styles. Students scored 20% higher on the test scores when using an awareness instruction. © 2010 Elsevier Ltd. All rights reserved.